Analysis of Differentially Expressed Genes (DEGS) Related to Interleukin-17 Signaling for Biomarker Identification and Therapeutic Targets in Atopic Eczema - Fauziah, Siva; Veranita, Weri; Nurbaya, Siti; Sari, Puji (UI Scholars Hub, 2025)
Atopic eczema, also known as atopic dermatitis, is a chronic inflammatory skin condition characterized by itchy, red, and swollen skin. It is often associated with other atopic diseases such as asthma and hay fever. Interleukin-17 (IL-17), a pro-inflammatory cytokine, plays a crucial role in various inflammatory and autoimmune conditions, including atopic eczema. This study aims to identify potential therapeutic targets for managing atopic eczema based on the analysis of differentially expressed genes (DEGs). The expression of these gene targets was subsequently validated for their potential as biomarkers. Additionally, upstream regulator protein (URP) searches for the resulting DEGs were conducted. DEG analysis of the Gene Expression Omnibus (GEO) dataset, GSE6012 (atopic eczema vs. healthy donor skin), revealed that genes related to IL-17 signaling—FOSL1, MMP1, DEFB4B, S100A7, S100A8, and S100A9—can serve as biomarkers for atopic eczema with sensitivity and specificity values of 1.000. URP analysis suggested that inhibition of IL1A and NOG, as well as TGFB1 activity, are potential therapeutic targets to downregulate these six DEGs, thereby restoring their expression to the levels observed in healthy skin.